Beyond academics: Dropout prevention summer school programs in the transition to secondary education. (October 2019) - Vinas-Forcade, Jennifer; Mels, Cindy; Valcke, Martin; Derluyn, Ilse
Highlights: Summer schools help students prepare for the transition into secondary school. Positive peer and teacher-students relationships are fostered by summer schools. Summer schools provide early familiarization with secondary school structure. The extension of the school year helps support students at higher risk of failure. Distinction of academic and recreational components helps first-generation students. Abstract: Educational transitions, for example from primary to secondary school, have been associated with school drop-outs, particularly for students from lower socio-economic backgrounds. As a response, some educational systems have implemented summer programs, although with mixed results. Yet, these evaluations mostly assess programs' quantitative impact on academic outcomes. This article therefore aims at an in-depth exploration of the benefits and challenges of a Uruguayan summer school program for preventing dropout in the transition to secondary school. Results underpin summer peer interactions, teacher-student relations and extra-curricular activities shape positive pre-entry expectations of at-risk students, which secondary schools cannot always fulfill.